Persepsi guru dan pelajar terhadap persekitaran pembelajaran konstruktivisme untuk mata pelajaran Teknologi Maklumat dan Komunikasi - Lo, Yoon Mee; Bakar, Ab. Rahim; Wong, Su Luan (Universiti Putra Malaysia Press, 2008)
The purpose of this study was to assess teacher’s and student’s perceptions of constructivist learning environments for the subject Information Technology and Communication (ICT) at national secondary schools in Klang Valley. Teacher’s and student’s perceptions were measured in terms of five dimensions — Personal Relevance, Uncertainty, Critical Voice, Shared Control and Student Negotiation. A total of 440 students and 74 teachers were involved in this study. The results of this study showed that teachers and students considered the existence of the constructivist learning environment to be at the moderate level. In other words, the results suggest that constructivism is not practiced so effectively in the ICT teaching-learning environment. The results of the study also suggest that the majority of teachers and students perceived ICT as a subject that is ever changing but they do not perceive that students have shared control over their learning.